Fetus in Fetu in an Adult Female and Brief Review of Literature - Saroj Sharma; Prashant Kumar Gupta; Basanta Regmi; Aarti Gupta; Upasana Lamichhane (Case Reports in Radiology)
Fetus in fetu (FIF) is a very rare condition in which malformed fetus is found within the body of a living twin, most commonly within the retroperitoneum. It is a parasitic fetal twin of a diamniotic, monozygotic type. It should be differentiated from teratoma by the presence of organized vertebral column and appropriately arranged other organs or limbs around it. There is no such axial arrangement in teratoma, which has also got definite malignant potential. We report a case of FIF in a 21-year-old lady who presented late with nonspecific abdominal symptoms. Preoperative diagnosis of FIF in this case was made on computed tomography, and the patient underwent exploratory laparotomy with complete excision of mass. The excised mass in a sac was proven to be FIF on the basis of gross and histopathological examination. Surgical excision is the ideal treatment even teratoma being the differential diagnosis.